2017
DOI: 10.3390/genes8120371
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Conditioned Medium Modulates Apoptotic and Stress-Related Gene Expression, Ameliorates Maturation and Allows for the Development of Immature Human Oocytes after Artificial Activation

Abstract: The aim of the present study was to determine whether mesenchymal stem cell-conditioned medium (MSC-CM) modulates apoptotic and stress-related gene expression, and ameliorates maturation and developmental potential of immature human oocytes after artificial activation. A total of 247 surplus immature germinal vesicle (GV) oocytes obtained from infertile women were allocated into two in vitro maturation (IVM) groups: 1: GV oocytes (n = 116) matured in vitro (fIVM), and 2: GV oocytes (n = 131) that were vitrifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Additionally, they proved the conditioned media have a promising ability to improve IVM of polycystic ovary syndrome oocytes. In addition, human umbilical cord stem cells derived conditioned medium showed potential efficacy in terms of improving oocyte maturation and mRNA expression related to apoptosis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they proved the conditioned media have a promising ability to improve IVM of polycystic ovary syndrome oocytes. In addition, human umbilical cord stem cells derived conditioned medium showed potential efficacy in terms of improving oocyte maturation and mRNA expression related to apoptosis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The parthenogenesis induced with ionomycin was enhanced in the presence of CM in comparison with AMM. In the AMM, there was no seen the develeopment of blastocyst, whereas 5% blastocyst development was reported in the CM in the non-vitrified oocytes (Akbari et al, 2017). In another clinical study, the effects of CM of ADSCs on sperm motility and viability were searched.…”
Section: Discussionmentioning
confidence: 99%
“…Because, the MSCs secreted the cytokines and growth factors into the CM, and it is thought taht the CM will have an improvement effect on the reproductive cells and organs (Ullah et a., 2015;de Olivera Bezerra et al, 2019;Yang et al, 2019). Bader et al, reported that the CM of ADSCs rised the sperm motility in vitro condition, whereas Akbari et al, appointed that CM of human umblical cord mesenchymal stem cells prometed the oocyte maturation and the formation of blastocyst (Akbari et al, 2017;Bader et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…developmental potential of artificially activated the maturation and developmental potential of immature human oocytes after the activation (Akbari et al, 2017). Thus suggesting that perhaps conditioned medium from HUMSCs in vitro, induced by the same factors in vivo, could also be therapeutic for the disease.…”
Section: Paracrine Effects Of Human Umbilical Cord Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Compared with normal medium, HUMSCs-CM protected both frozen and thawed ovarian tissues ( Jia et al, 2017 ), and in a model of cisplatin-induced ovarian injury, HUMSCs-CM alleviated cisplatin-induced follicular failure and maintained fertility ( Hong et al, 2020 ), and in follicular development, HUMSCs-CM improved the maturation and developmental potential of artificially activated the maturation and developmental potential of immature human oocytes after the activation ( Akbari et al, 2017 ). Thus suggesting that perhaps conditioned medium from HUMSCs in vitro , induced by the same factors in vivo , could also be therapeutic for the disease.…”
Section: The Role Of Human Umbilical Cord Mesenchymal Stem Cells In the Treatment Of Ovarian Agingmentioning
confidence: 99%